Development of a 'patient information leaflet' for use following assessment of patients with reported or suspected paracetamol overdose in the UK. Issue 6 (1st September 2014) - Potter, Thomas; Chan, Wui Ling; Archer, John R. H.; Barrett, Jessica; Dargan, Paul I.; Wood, David M.
Abstract The aim of this study was to design an information leaflet for patients with paracetamol overdose based on Medicines and Healthcare products Regulatory Agency guidance and to assess its readability. A two‐sided one page information leaflet was designed for patients being discharged from hospital after a paracetamol overdose. Patients presenting with an acute paracetamol overdose, irrespective of whether they were treated or not, were recruited to read the leaflet and then answer a brief structured questionnaire based on the leaflet. The readability of the information leaflet was assessed using the Flesch reading ease score. Thirty patients (15 male, 12 female, 3 not recorded; mean age 38 ± 13.0 years) were recruited, wherein 100% of patients reported the language used was understandable, 96.6% knew which symptoms would require urgent medical review after discharge and 100% of patients knew the liver was affected by paracetamol. The Flesch reading ease score was 67.6 (out of a maximum of 100), equivalent to a UK reading age of 10–11years old. Our information leaflet for all patients being discharged after paracetamol overdose was well received by patients, provided them with the required knowledge and had an appropriate reading age based on UK literacy rates. We would recommend that this leaflet could be used as a template on a national level, localized to individual hospitals, to improve patient knowledge of paracetamol toxicity, and facilitate early medical review in the event of deterioration following discharge from the hospital.